An experimental study of FRP truss side plate joint. (15th February 2023) - Zou, Xingxing; Feng, Yu; Zhong, Rui; Fang, Tingchen; Wang, Jingquan
Highlights: Prosed a steel U-shaped gusset plate (SUGP) FRP truss joint. Compared the response of the SUGP joint with two bolted joints. Investigated the effects of different variables on the behavior of the SUGP joint. Abstract: Ultra-high performance concrete (UHPC) slab - fiber reinforced polymer (FRP) truss hybrid beam has been proved as an effective and advanced bridge system. However, the limited shear strength and the significantly lower transverse properties compared with its longitudinal counterparts result in low rigidity and load carrying capacity of bolted FRP truss joints, which governs the overall performance of the UHPC slab- FRP truss hybrid beam. A FRP truss side plate joint was proposed which integrates a steel U-shaped gusset plate (SUGP) to reinforce the traditional bolted joint. The proposed joint outperformed the conventional bolted joints in terms of the failure mode, load carrying capacity, and stiffness. The load carrying capacity of the proposed joint can be improved by up to 63% and the ultimate deflection was reduced by up to 33%. The effects of a variety of key design parameters, including adhesive, bolt diameter, pre-torque, and length and thickness of the gusset plate, on the performance of the SUGP joint were evaluated. Test results showed that: (i) the adhesive between the pultruded FRP profiles and the steel gusset plate could increase both the initial stiffness and ultimate load carrying capacity of the steel SUGP joint; (ii) length and thickness of the steel gusset plate did not result in notable difference in the behavior of the steel SUGP joint for the range of parameters investigated herein; and (iii) application of pre-tightening torque within the thread of the bolts slightly improved the load carrying capacity but significantly improved the ductility of the steel SUGP joint.